2011
DOI: 10.3732/ajb.1000369
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rhizosphere fungi from selenium hyperaccumulator and nonhyperaccumulator plants along the eastern Rocky Mountain Front Range

Abstract: Even though Se is a commonly used antifungal agent, these results suggest that rhizosphere fungi from seleniferous habitats have widespread Se tolerance, likely an adaptive advantage in their Se-rich habitat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…We did not address this, but different nodule [Se] between Se-hyperaccumulators and nonhyperaccumulators could act as a selective force for rhizobial symbionts. Rhizosphere fungal communities from seleniferous soils have been shown to have increased Se tolerance and some may be considered habitat specialists that associate with Se-hyperaccumulators ( Wangeline et al, 2011 ). Tolerance to inorganic Se forms at levels that well-exceed the nodule [Se] in all our specimens have been observed in some rhizobia isolates in vitro ( Kinkle et al, 1994 ).…”
Section: Se Localization and Speciation In Nodules -Selenium Wasmentioning
confidence: 75%
“…We did not address this, but different nodule [Se] between Se-hyperaccumulators and nonhyperaccumulators could act as a selective force for rhizobial symbionts. Rhizosphere fungal communities from seleniferous soils have been shown to have increased Se tolerance and some may be considered habitat specialists that associate with Se-hyperaccumulators ( Wangeline et al, 2011 ). Tolerance to inorganic Se forms at levels that well-exceed the nodule [Se] in all our specimens have been observed in some rhizobia isolates in vitro ( Kinkle et al, 1994 ).…”
Section: Se Localization and Speciation In Nodules -Selenium Wasmentioning
confidence: 75%
“…The accumulation Se in peripheral tissues of young leaves and reproductive organs may be a strategy to accumulate high concentrations of Se as SeCys 2 [45], [47][55]. Also, rhizospheric bacteria may contribute to the high ability to accumulate Se or SeCys 2 in tissues [56], [57]. Further study should be carried out on distinguishment special SeCys 2 synthase or enhancement by rhizospheric microorganisms to explain high SeCys 2 accumulation in C. hupingshanesis .…”
Section: Discussionmentioning
confidence: 99%
“…were shown earlier to be 50% inhibited in growth on medium with 50 mg Se kg 21 dry weight, and Se accumulation effectively protected plants against these pathogens (Hanson et al, 2003). In a recent study by Wangeline et al (2011), the growth of an Aspergillus leporis strain isolated from the rhizosphere of a nonhyperaccumulator plant growing in a nonseleniferous habitat was reduced by 50% when exposed to 30 mg Se L…”
Section: Discussionmentioning
confidence: 99%
“…A litter decomposition study conducted on seleniferous soil showed that native A. bisulcatus litter naturally high in Se decomposed faster and harbored higher numbers of microbes and microarthropods than low-Se alfalfa (Medicago sativa) litter collected in the same area . Furthermore, Se-tolerant fungi were isolated from the rhizosphere of hyperaccumulators A. bisulcatus and S. pinnata (Wangeline and Reeves, 2007), and rhizosphere fungi from hyperaccumulators growing on seleniferous soil were significantly more Se tolerant than fungi from nonseleniferous areas (Wangeline et al, 2011).…”
mentioning
confidence: 99%